Sex and gender affect immune aging - Calabrò, Anna; Accardi, Giulia; Aiello, Anna; Caruso, Calogero; Candore, Giuseppina (Frontiers in Aging, 2023)
The proposed review aims to elucidate the intricate interplay between biological factors (sex differences) and socially constructed factors (gender differences) in the context of immune aging. While the influence of biological differences between men and women on various aspects of immune responses has long been recognized, it is crucial to acknowledge that gender, encompassing the social and cultural roles and expectations associated with being male or female, also significantly shapes these processes. Gender can either accelerate immune aging or promote longevity. By recognizing the impact of both biological and social factors, this paper seeks to offer a comprehensive understanding of why men and women may experience divergent trajectories in immune aging and varying outcomes in terms of longevity. Discrepancies in perceived roles of the sexes, both within families and at work, contribute to differing patterns of antigen exposure. Additionally, variations in micronutrient intake and access to preventive healthcare facilities may exist. Health promotion knowledge often correlates with educational attainment, which is unequally represented between males and females in many cultures and across generations in the Western world. In countries without a universal healthcare system, access to healthcare relies on family prioritization strategies to cope with economic constraints, potentially limiting access to specific treatments and affecting immune responses negatively. As a result, both biological factors and social and behavioural factors associated with gender contribute to disparities in immune responses, susceptibility to infections, autoimmune diseases, and vaccine responses among older individuals. However, as demonstrated by the COVID-19 pandemic, older females exhibit greater resilience to infections than older males. Given the crucial role of the immune system in achieving longevity, it is not surprising that women live longer than men, and the number of female centenarians surpasses that of male centenarians.